THE IMPLEMENTATION OF WADI’AH CONTRACT ON NUSA SAVINGS PRODUCTS ACCORDING TO DSN FATWA NO. 02/DSN–MUI/IV/2000 - Safitri, Diah Intan; Yohani, Yohani; Moegiri, Moegiri (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2023)
The Implementation of Wadi'ah Contract on Nusa Savings Products According to DSN Fatwa No. 02/DSN – MUI /IV/2000 at BMT Nurussa'adah Pekalongan Islam encourages a muslim to save, because by saving means a muslim prepares himself for the implementation of future planning as well as for dealing with unexpected things. This study has discussed the whether the implementation of Wadi’ah contract on Nusa Savings product is in accordance with the pillars and conditions of the Wadi'ah contract in Islamic syari'at and in the provisions of the DSN MUI Fatwa No.02 DSN-MUI/IV/2000 Concerning Savings. The study aims to determine how the implementation process of Wadi’ah contract is, starting from registration and administration process, the deposit and withdrawal, and how the contract ends and conformity with Islamic law and the provisions of the Fatwa DSN MUI No. 02 DSN-MUI/IV/2000 Concerning Savings. The method was quantitative study with descriptive analysis. Collecting data method used documentation and direct interview with operational management of BMT and the consumers of Nusa Savings to obtain data source as a whole. The implementation of Wadi’ah at BMT Nurussa’adah Pekalongan technically and the sharia concept is in accordance with the DSN MUI Fatwa No.02 DSNMUI/ IV/2000 Concerning Savings. In implementing this contract, it is in accordance with the pillars and sharia in Islam.